The Paradigm of Physical Punishment from the Perspective of Islamic Education and Its Implementation in Indonesia and Malaysia - Ibnu Fitrianto; Nurhuda Alfina Layalin; Aunillah Ahmad (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study explores the paradigm of physical punishment within Islamic educational institutions in Indonesia and Malaysia, examining its theological justifications, cultural roots, institutional frameworks, and practical implications. Using a qualitative comparative case study approach, data were collected through interviews with educators, students, and community leaders; classroom observations; and analysis of policy and curriculum documents. The findings indicate that while both countries share normative references to Islamic teachings, their interpretations and applications of physical discipline vary. In Indonesia, especially in traditional pesantren, physical punishment is often viewed as a tool for moral formation under the concept of ta’dib. In contrast, Malaysia demonstrates a gradual shift toward more compassionate and rights-based approaches to discipline, driven by stronger regulatory frameworks and public discourse. However, challenges such as lack of teacher training, uneven policy implementation, and persistent cultural beliefs continue to shape practices in both countries. The study concludes that a transformative approach to Islamic education requires balancing religious values with child protection principles and contemporary pedagogical thought, encouraging a shift toward holistic, non-violent educational practices.